Tindak Tutur Kata Sapaan Masyarakat Angkola Di Kota Padangsidimpuan - Siti Meutia Sari; Tinur Rahmawati Harahap; Nursaima (Yayasan Perguruan Kampus, 2024)
Speech acts are a theory of language use put forward by John Langshaw Austin (1962) in his book entitled How to do things with words. In speech events, a number of components of speech are found. There are 16 components put forward by Hymes (1974), namely message form, message content, setting, scene, message sender, speaker, message receiver, interlocutor, intent, purpose, key, channel, form of speech, interaction norms, norms interpretation, and genre. These 16 elements are summarized into 8 speech components with the English acronym